2016
DOI: 10.1164/rccm.201507-1414oc
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Expansion of Human Epithelial Stem Cells Suitable for Airway Tissue Engineering

Abstract: Rationale: Stem cell-based tracheal replacement represents an emerging therapeutic option for patients with otherwise untreatable airway diseases including long-segment congenital tracheal stenosis and upper airway tumors. Clinical experience demonstrates that restoration of mucociliary clearance in the lungs after transplantation of tissue-engineered grafts is critical, with preclinical studies showing that seeding scaffolds with autologous mucosa improves regeneration. High epithelial cell-seeding densities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
214
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 181 publications
(222 citation statements)
references
References 63 publications
6
214
2
Order By: Relevance
“…We attempted cell culture from 12 patients (median age = 75 years, range = 58–90 years), whose surgically resected primary lung adenocarcinoma (LUAD) tumors (stage II [ n  = 9] or III [ n  = 3]) are being analyzed in the on‐going Tracking Cancer Evolution through Therapy (TRACERx) clinical study,14, 15 using a published protocol 17. We obtained primary epithelial cell cultures that could be passaged from 10 (83.3%) of these.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We attempted cell culture from 12 patients (median age = 75 years, range = 58–90 years), whose surgically resected primary lung adenocarcinoma (LUAD) tumors (stage II [ n  = 9] or III [ n  = 3]) are being analyzed in the on‐going Tracking Cancer Evolution through Therapy (TRACERx) clinical study,14, 15 using a published protocol 17. We obtained primary epithelial cell cultures that could be passaged from 10 (83.3%) of these.…”
Section: Resultsmentioning
confidence: 99%
“…Protocol differences exist between the aforementioned studies: key studies have used inactivated human dermal fibroblasts7, 8 as feeder layers rather than the mouse embryonic fibroblasts often used in those that see normal cell expansion and it has also been possible to transition tumor cell cultures off feeder layers after 6 months of culture establishment 8. We have previously demonstrated that adult human lung fibroblasts do not support long‐term normal airway epithelial cell expansion in the same way as 3T3‐J2 cells17 so the use of adult and/or human feeder cells might favor tumor cell expansion. Relevant biological differences might also exist between mitotic inactivation using irradiation4, 9 rather than mitomycin C, as used here.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, for urgent re-cellularization of bioengineered scaffolds there is often insufficient time for isolation and expansion of autologous airway epithelial cells to obtain the required cell numbers by standard methods. Thus, Butler and colleagues have developed a novel and faster method to obtain larger numbers of functional airway basal cells (15). Based on existing work in the stem cell field (16), they compared a co-culture with mitotically inactivated 3T3-J2 fibroblast feeder cells in the presence of Rho-associated protein kinase (ROCK) inhibition (inhibitor Y27632) (3T3 + Y), to the classical expansion in bronchial epithelial growth medium (BEGM) (15).…”
Section: Epithelial Stem Cells and Airway Tissue Engineeringmentioning
confidence: 99%
“…Thus, Butler and colleagues have developed a novel and faster method to obtain larger numbers of functional airway basal cells (15). Based on existing work in the stem cell field (16), they compared a co-culture with mitotically inactivated 3T3-J2 fibroblast feeder cells in the presence of Rho-associated protein kinase (ROCK) inhibition (inhibitor Y27632) (3T3 + Y), to the classical expansion in bronchial epithelial growth medium (BEGM) (15). Basal cells cultured under 3T3 + Y conditions proliferated faster than those grown in BEGM, retained their normal karyotype after 6 weeks in culture, were able to differentiate into a pseudostratified epithelium at the air-liquid interface, as well as to form tracheospheres, also in late passages (15).…”
Section: Epithelial Stem Cells and Airway Tissue Engineeringmentioning
confidence: 99%